Avaliação de transferência de calor e massa em biorreator Airlift de bancada para a produção de ácido clavulânico - Cerri, Marcel Otávio (2005)
The importance of the airlift bioreactor has grown in the biotechnology field by aspects as high oxygen transfer, with power input low. In this work were study the conditions heat and mass transfer, as well as the condenser efficiency in the water retention, of an airlift bench bioreactor of internal circulation of useful capacity 6 L. Such bioreactor is endowed with hollow draft tube working as a heat charger for temperature control and of aspersor type crosspiece for aspersion of air. Values of the heat transfer global coefficient (U) were certain in different operation conditions starting from applied energy balance in the system after the same to reach the steady state. Values of U varied in the range from 300 to 700 W.m-2.°C-1, showing that the device of thermal change proposed was efficient to heat removal. The results were correlated with the water flow inside the draft tube and with the feeding air flow in the bioreactor. After this stage, it was evaluated water drags of the bioreactor system plus condenser in different conditions of air flow and temperatures in the bioreactor and in the condenser. The condenser was shown efficient in the water retention, obtaining efficiency superior values to 80%, but it didn't solve the problem of water loss by water drag for the high air flows in that the airlift bioreactor is operated. The variable air flow was the variable that influenced more significantly water drags. The transfer oxygen was evaluated through the oxygen transfer volumetric coefficient (kLa). For comparison, kLa values were obtained in the airlift bioreactor operated in a range of specific feeding air flow from 1 to 5 vvm and in conventional bioreactor of 4 L, in different agitation conditions (600, 800 and 1000 rpm) and aeration (0,5 and 1,0 vvm). Two methods for kLa determination were employees, the sulfite method and the dynamic method considering the delay of the electrode answer. This last one that generated results between 2 and 6 times inferior, depending of bioreactor type, because it evaluates the kLa in coalescent media, similar to most of the media fermentation. Finally, to validate the use of the system as bioreactor, cultivations with Streptomyces clavuligerus seeking to the production of clavulanic acid, a potent inhibitor of β-lactamase, enzyme producted by patogenics microorganism that broke β-lactamic rings of antibiotics. Four cultivations were accomplished, two in airlift bioreactor and two in bioreactor conventional (Bioflo III) in two different conditions of oxygen transfer (kLa) and the results were compared in terms of clavulanic acid production. The maximum clavulanic acid concentrations obtained in the cultivations in airlift bioreactor were superior those obtained in conventional bioreactor, with minors consistence index (K), showing larger shear rate in the airlift bioreactors in the same conditions of transfer oxygen. In global terms, the obtained results suggest that bioreactor as the most appropriate for this cultivation type, justified for the appropriate heat and mass transfers formed an alliance with the smallest energy consumption.